The main trends in the use of documents in the Central State Archive of Scientific and Technical Documentation of the Republic of Kazakhstan - SABLIN, Syrym; MAGIER, Dariusz (Historia i Świat, 2023)
According to the state program ‘Archive 2025’ for wide access to archival documents in Kazakhstan the web portal ‘Unified electronic archive of documents was launched’. At the moment, there is no information on the funds of the Central State Archive of Scientific and Technical Documentation on this site yet, but it is planned to add it to the electronic catalog in the future. For the successful implementation of data on documents stored in the funds of the Central State Archive of Scientific and Technical Documentation, it is necessary to analyze which types of documents are most popular among the archive users (both in the reading room and when executing information requests by the archive) and which need to be translated into electronic format as a priority, for this purpose, the reports of the Central State Archive of Scientific and Technical Documentation were studied for the period from 1974 to 2021.